EU-enlargement and labour relations: New trends in Poland, Czech and Slowak Repubik - Jochen Tholen; Ludovit Czíria; Eike Hemmer; Zdenka Mansfeldová (Institut Arbeit und Wirtschaft (IAW), Universität Bremen und Arbeitnehmerkammer Bremen, 2003)
Die Auswirkungen von Direktinvestitionen deutscher Unternehmen auf die Arbeitsbeziehungen in Mittel-/Osteuropa Am Beispiel ausgewählter Länderfallstudien in Polen, der Tschechischen und Slowakischen Republik In diesem Forschungsprojekt untersucht das Institut Arbeit und Wirtschaft die Veränderungen der Arbeitsbeziehungen in Betrieb und Unternehmen der EU-Beitrittsländer unter dem Einfluß ausländischer Direktinvestitionen. Die Untersuchung erstreckt sich auf die Branchen Metall/Stahl, Chemie/Energie und die Nahrungsmittel produzierende Industrie in drei ausgewählten Mittelosteuropäischen Ländern (Polen, Tschechische Republik und Slowakei). Das Projekt ist anwendungsorientiert und setzt sich das Ziel, an einem Netzwerk von Wissenschaftlern und Praktikern, die mit den Arbeitsbeziehungen befasst sind, mitzuwirken. Dazu dienen eine Reihe von Hearings und Konferenzen in den beteiligten Ländern. [...] Im vorliegenden Arbeitspapier präsentieren die beteiligten Wissenschaftler einen Überblick über die Entwicklung der Arbeitsbeziehungen in ihren jeweiligen Ländern. Die Reports beruhen auf der Auswertung existierender Forschungsberichte und eigenen Untersuchungen. Im letzten Teil erfolgt eine zusammenfassende Bewertung der Unterschiede und der Gemeinsamkeiten in den Arbeitsbeziehungen der drei Länder. Das Projekt wird finanziell gefördert durch die Hans-Böckler-Stiftung und die Otto Brenner Stiftung. – – The Impact of Foreign Direct Investments of German Companies on the Labour Relations in Middle-East-European Countries - Taking the Examples of Poland, the Czech Republic and Slovakia The controversial themes of "free movement of labour", "free movement of services", "costs for adaptation" dominate the discussion about the Eastern enlargement of the EU. The indirect long-term economic and political benefits of the EU enlargement as well as the costs for nonenlargement remain untouched. The Foreign Direct Investments can play a considerable role to modernise the economy and the social welfare state in Middle/East Europe. But this means, that other social actors than the state as trade unions, employers' associations, company management and employee representatives at works and company level have to take over an enormous responsibility. In the wake of foreign direct investments in the CEE countries, social actors from West European as well as from Central and eastern European countries can and must contribute to foster a "social Europe" more than ever before. [...] A research project, coordinated by the Institute Labour and Economy, University of Bremen aks for The Impact of Foreign Direct Investments of EU based Companies on Labour Relations in EU Candidate Countries". It covers the chemical, energy, metal, steel and food processing industry in three selected countries of Central and Eastern Europe, Poland, the Czech Republic and Slovakia. This project is an applied research, advisory and qualification project which also has the character of a model study. Through organizing hearings and conferences of results there should be closer connection to network with researchers and practitioners who are concerned with labour relations. Furthermore considerations regarding dealing with and examining the mutual effects between foreign direct investments and labour relations in the three CEE countries should be discussed and worked on with company and trade union representatives and other experts. The objective of the study are the labour relations at plant/company level, considering the supra company and legal levels too, if necessary. The empirical work of the study concentrates on evaluation of already existing surveys, expert interview on companies' and supra-companies level. The papers, presented herein, collect preliminary studies of the development of labour relations in the three countries, contributed by the partners in Poland, the Czech Republik and Slovakia. They are based on a evaluation of existing surveys and own research and should be taken as a framework for further investigation and as incentives for the following working packages of the project. In the summary there will be taken a look on the diversities and interfaces of Industrial Relations in the respective countries. Sponsored by Hans-Böckler-Foundation and Otto Brenner Foundation.
Keywords: 330; Arbeitsbeziehungen; Auslandsinvestition; EU-Mitgliedschaft; Tschechien; Polen; Slowakei